Operation of The Educational Institution Student Care and Support the Special Education Bureau Group 7 - Klubsrion, Nanphiphat; Kaewmano, Chaowanee (Interdisciplinary Academic and Research Journal, 2025)
Background and Aims: An academic paper on the operation of the student support system of educational institutions affiliated to the Office of Special Education Administration, Group 7, with the objectives of 1) to study the operation of the student support system of educational institutions affiliated to the Office of Special Education Administration, Group 7, 2) to compare the operation of the student support system of educational institutions affiliated to the Office of Special Education Administration. Group 7 Methodology: Classification by gender, educational background, experience, work, size of educational institution, and type of educational institution under the Office of Special Education Administration, Group 7 and 3) Study on the guidelines for the operation of the student support system of educational institutions affiliated to the Office of Special Education Administration, Group 7. The size was determined by sending the tool to Ratchaprachanukroh School, affiliated with the Office of Special Education Administration, Group 8, with a consistency value of .67 – 1.00 and a confidence value of .963 Results: 1) The operation of the student support system of educational institutions affiliated to the Office of Special Education Administration, Group 7, is at a high level overall. 2) The operation of the student support system of educational institutions affiliated to the Office of Special Education Administration, Group 7, is classified according to different variables of educational qualifications and work experience. It was found that the overall picture was not different, and the gender was different. When looking at each aspect, it was found that there was a statistically significant difference in getting to know students individually at the .01 level and in terms of prevention, assistance, and problem solving. There was a statistically significant difference at the .05 level. When looking at each aspect, it is found that in terms of promoting and developing students. There was a statistically significant difference at the .05 level and in terms of prevention, rescue, and problem solving. There is a statistically significant difference at the level of .01. 3) Guidelines for the systematic operation of student support of educational institutions: Factors affecting the systematic operation of student support of educational institutions affiliated to the Office of Special Education Administration, Group 7, should be studied Conclusion: The systematic operation of student care and support of educational institutions. Factors affecting the systematic operation of student care and support of educational institutions affiliated to the Office of Special Education Administration should be studied.